Identification of two new HLA class I alleles in Italian bone marrow donors: A*31:125 and B*44:269. (19th December 2017) - Sciarrino, R.; Fornaciari, S.; Mariotti, M. L.; Scatena, F.; Curcio, M.
Abstract : Two novel alleles, HLA‐A*31:125 and HLA‐B*44:269, are described in Italian bone marrow donors.